Development of the Bestin Android App to Improve the Reading Qur’an of Students Elementary Schools - Ani Nur Aeni; Hana Siti Salmah; Dinda Shalsa Agistie; Siti Rahmah Nurainun; Norhazlin Muhammad (Al Ibtida: Jurnal Pendidikan Guru MI, 2026)
Background: The integration of mobile technology into elementary education has created new opportunities for improving students' engagement and learning outcomes. However, Quran learning at the elementary level remains largely dependent on conventional teaching methods, which often provide limited opportunities for interactive, self-paced, and technology-supported practice. Aims: This study aims to develop and evaluate the effectiveness of an Android-based learning application called Bestin (Belajar Surah at-Tin) in improving the ability of fourth-grade elementary school students to read Surah At-Tin Methods: This study employed the Design and Development (D&D) research method using the ADDIE model, consisting of five stages: analysis, design, development, implementation, and evaluation. The developed application was validated by content and media experts and subsequently tested with 24 fourth-grade elementary school students to evaluate its usability and effectiveness. Results: Based on the content expert validation showed a feasibility score of 91.25%, while media experts gave a perfect score of 100%. A trial involving 24 fourth-grade elementary school students received very positive feedback the application was considered interesting, easy to use, and helpful in understanding the material. Student evaluation results showed an average score of  92,5 indicating a high level of acceptance and effectiveness. Conclusion: The Bestin Android application is an effective, innovative, and interactive medium for Quran learning that significantly enhances students' Quran reading skills and learning outcomes. The findings suggest that integrating mobile learning technologies into elementary Islamic education can enrich students' learning experiences and promote collaborative support among schools, teachers, and parents.